KONTRIBUSI TEORI IBN AL-SHĀṬIR DALAM PERKEMBANGAN TRADISI ILMIAH ASTRONOMI ISLAM - S Sakirman; Muslich Shabir (Universitas Islam Negeri (UIN) Walisongo Semarang, Indonesia, 2017)
This paper traces the roots of the scientific tradition of astronomy in a classical century that marked the rise of Islamic civilization in the midst of Western darkness in a philosophical-historical perspective. The study focussed on translation activities in the eighth century to the peak of astronomical scientific activity that is divided into two major schools; the astronomical-mathematical school of the East and the astronomical-philosophical schools of the Western world to the Islamic Caliphate. The Greek astronomical tradition is basically dominated by Aristotelian thought that states that the universe is organized into a set of concentric spheres each carrying a star and spinning around the earth. The Earth is still and becomes the center of the universe. Ptolemy adopted the two basic principles of Aristotle, ie the earth dwells at the center of the universe and the motion of heavenly bodies must be represented by a set of perfectly uniform circular motions. From the results of historical studies on the development of Muslim astronomy in the classical century can be seen that the peak of scientific progress in the Western world can not be separated from the point of zenit for the advancement of science developed by Muslim scientists. Efforts made by Western scientists in enriching the astronomical treasury is inseparable from the step of translation through intensive scientific studies that gave birth to a variety of monumental works in the history of astronomy.Tulisan ini melacak akar tradisi ilmiah astronomi pada abad klasik yang menandai majunya peradaban Islam di tengah-tengah kegelapan Barat dalam perspektif historis-filosofis. Kajian difokuskan pada aktivitas penerjemahan pada abad kedelapan hingga puncak kegiatan ilmiah astronomis yang terbagi dalam dua mazhab besar; mazhab astronomis-matematis di Timur dan mazhab astronomis-filosofis di dunia Barat pada kekhalifahan Islam. Tradisi astronomi Yunani pada dasarnya didominasi pemikiran Aristotelian yang menyatakan bahwa alam semesta diatur menjadi satu set bola konsentris masing-masing membawa bintang dan berputar di sekitar bumi. Bumi berposisi diam dan menjadi pusat alam semesta. Ptolemeus mengadopsi kedua prinsip dasar Aristoteles tersebut, yaitu bumi diam di pusat alam semesta dan gerak benda-benda langit harus diwakili oleh satu set gerakan melingkar sempurna yang seragam. Dari hasil kajian historis atas perkembangan astronomi muslim pada abad klasik dapat diketahui bahwa puncak kemajuan ilmu pengetahuan di dunia Barat tidak lepas dari titik zenit atas kemajuan ilmu pengetahuan yang dikembangkan oleh ilmuwan Muslim. Upaya yang dilakukan ilmuwan Barat dalam memperkaya khazanah astronomi tidak terlepas dari langkah penerjemahan melalui pengkajian ilmiah yang intensif sehingga melahirkan berbagai karya-karya monumental dalam sejarah astronomi.